STRATEGI GURU PAI DAN BUDI PEKERTI DALAM AKOMODASI PEMBELAJARAN HAFALAN DOA SEHARI-HARI SISWA DENGAN HAMBATAN BELAJAR DI SEKOLAH DASAR - Dwi Anandyah Purnama Anasputri; Nur Azizah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning to memorize daily prayers for students with learning disabilities requires adaptive instructional strategies that accommodate their diverse learning needs. This study aimed to describe the strategies employed by Islamic Religious Education and Character Education teachers in accommodating daily prayer memorization for students with learning disabilities in elementary schools in Muara Ancalong District. This study employed a descriptive qualitative approach. Data were collected from primary and secondary sources through in-depth interviews, observations, and document analysis. The research focused on instructional approaches, prayer memorization techniques, learning media and resources, as well as the challenges and solutions encountered during the learning process. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented various instructional accommodation strategies tailored to students' learning characteristics, including flexible teaching approaches, repetitive memorization (drilling), individualized memorization targets, one-on-one guidance, and the use of visual media such as prayer posters placed in relevant locations. Teachers also addressed learning challenges through individualized support, simplified learning materials, gradual instruction, and continuous motivation. These strategies contributed to supporting the learning of daily prayer memorization for students with learning disabilities while fostering a more inclusive learning environment in Islamic Religious Education and Character Education classes. ABSTRAK Pembelajaran hafalan doa sehari-hari bagi siswa dengan hambatan belajar memerlukan strategi pembelajaran yang adaptif agar kebutuhan belajar setiap peserta didik dapat terakomodasi secara optimal. Penelitian ini bertujuan untuk mendeskripsikan strategi guru Pendidikan Agama Islam dan Budi Pekerti dalam mengakomodasi pembelajaran hafalan doa sehari-hari bagi siswa dengan hambatan belajar di sekolah dasar di Kecamatan Muara Ancalong. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Data diperoleh dari sumber primer dan sekunder melalui wawancara mendalam, observasi, dan studi dokumentasi. Fokus penelitian meliputi strategi pendekatan pembelajaran, teknik hafalan doa, penggunaan media dan sumber belajar, serta problematika dan solusi dalam pelaksanaan pembelajaran. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru menerapkan berbagai strategi akomodasi pembelajaran yang disesuaikan dengan karakteristik siswa, meliputi penggunaan pendekatan pembelajaran yang fleksibel, teknik hafalan melalui pengulangan (drilling), penetapan target hafalan sesuai kemampuan siswa, pendampingan secara individual, serta pemanfaatan media visual berupa poster doa pada lokasi yang relevan. Guru juga mengatasi berbagai kendala melalui pendekatan personal, penyederhanaan materi, pembelajaran bertahap, dan pemberian motivasi secara berkelanjutan. Strategi tersebut berkontribusi dalam mendukung pembelajaran hafalan doa sehari-hari bagi siswa dengan hambatan belajar sekaligus mendorong terwujudnya pembelajaran Pendidikan Agama Islam dan Budi Pekerti yang lebih inklusif.